Clinical efficacy of unicompartmental knee arthroplasty on limb swelling, pain, and functional rehabilitation in knee osteoarthritis patients - Xiangtao Zhang; Yongbin Han; Qingbing Bai; Tong Li; Fei Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Knee osteoarthritis (KOA) is common in middle-aged and elderly individuals, leading to progressive cartilage degeneration, pain, and impaired mobility. Objective To investigate the effect of unicompartmental knee arthroplasty (UKA) on swelling and pain of affected limbs and functional rehabilitation in patients with KOA. Methods One hundred KOA patients treated in our hospital from August 2022 to December 2024 were selected and divided into a test group (n = 48) receiving UKA and a matched group (n = 52) receiving total knee arthroplasty (TKA). The ROM, HKA, circumferences 10 cm below and above the midpoint of the patella, HSS score, VAS score, and the European Cancer Treatment Research Organization Quality of Life Scale (EORTC QLQ-C30) score were compared before and after operation. Results At 6 months postoperatively, the HSS score and ROM were significantly higher in the test group (92.21 ± 7.10 points and 103.30 ± 5.50°) than in the matched group (P < 0.05), while HKA (2.33 ± 0.82°) was significantly lower (P < 0.05). On the 7th postoperative day, circumferences 10 cm below and above the patella were significantly reduced in the test group compared to the matched group (P < 0.05). The VAS score in the test group was lower (1.02 ± 0.34 vs. 3.20 ± 0.92, P < 0.05). The EORTC QLQ-C30 score was significantly higher in the test group (92.10 ± 7.82 vs. 81.18 ± 8.40, P < 0.05), indicating better quality of life. Complication rates did not differ significantly between groups (P > 0.05). Conclusion Compared with total knee arthroplasty, UKA demonstrates better short-term outcomes in relieving pain, reducing swelling, and promoting functional recovery in patients with knee osteoarthritis. These findings support UKA as an effective option for appropriately selected patients. However, the study is limited by its single-center design and short-term follow-up.